Virtual environments for powered wheelchair learner drivers: case studies. - Adelola IA; Cox SL; Rahman A (Technology & Disability, 2009)
Early intervention through the use of a powered wheelchair can meliorate the developmental experience of children with mobility impairment. It is therefore important to design an effective training and assessment strategy to facilitate the potentials of each child in readiness to drive the device. The use of virtual reality (VR) technology for wheelchair training purposes is therefore considered. The skills acquired during training in a virtual reality system should be observable in the functional activities of the learner. It is necessary to evaluate the degree and the permanence of the skills learnt from the virtual environment to other activities outside the training environment. The mode of evaluation applied during conventional wheelchair training could provide the basis upon which permanence of skills is determined after training in virtual reality. Thus, an induction factor is proposed as a measure of the transfer of powered wheelchair control skills from virtual reality to the functional activities of daily living by the learner. The outcomes show that virtual reality technology could offer an appropriate means of providing powered wheelchair training that can be tailored to the needs of the learner.